Empirical Investigations of the Role of Implicit Prosody in Sentence Processing. Issue 2 (February 2014) - Breen, Mara
Abstract Recently, psycholinguistics has seen an increase in the number of empirical studies investigating the role of implicit (silent) prosodic representations in reading. The current paper reviews studies from the last several years conducted to investigate Fodor's (2002) Implicit Prosody Hypothesis, which maintains that even during silent reading, readers generate representations of sentence intonation, phrasing, stress, and rhythm, and that these representations can affect readers' interpretation of the text. We argue that the accumulated evidence suggests that implicit prosody can influence online sentence interpretation and explore the implications of these findings for models of sentence processing.